Acidity tuning of montmorillonite K10 by impregnation with dodecatungstophosphoric acid and hydroxyalkylation of phenol - Garade, Ajit C.; Kshirsagar, V. S.; Mane, R. B.; Ghalwadkar, Ajay A.; Joshi, U. D.; Rode, C. V. (Applied Clay Science, 2010)
Acidity tuning of montmorillonite K10 (mont K10) was achieved by impregnating with dodecatungstophosphoric acid (DTP). The effect on the hydroxyalkylation of phenol was studied at 353 K with phenol to formaldehyde molar ratio of 5. The nature and strength of acid sites were determined by NH(3)-TPD measurement while the distribution of Brensted and Lewis acid sites expressed as B/L ratio, was determined by pyridine IR technique. Among various loadings of DTP (5-60%) studied for the hydroxyalkylation of phenol, 20% DTP/mont K10 showed the highest catalyst activity (90% selectivity to bisphenol F with 28% conversion of phenol). Both total concentration of acid sites and the distribution of acid sites in a high temperature region were required for the high bisphenol F selectivity. Our catalyst (20% DTP/Mont K10) could be recycled three times. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Acidity tuning; Dodecatungstophosphoric acid/Montmorillonite K10; Hydroxyalkylation; Impregnation; Temperature programmed desorption

Environmental potential applications of alkali metal exchanged zeolite x in carbon dioxide adsorption - Joshi, U. D.; Joshi, P. N.; Roh, H. S.; Yoon, W. L.; Shiralkar, V. P. (Research Journal of Chemistry and Environment, 2011)
The increasing atmospheric CO2 concentration, mainly caused by the Thermal Power Stations, Industrial sector and fossil fuel combustion, has led to consequences of global warming. Zeolitic adsorption processes is more promising, energy saving and viable method for CO2 removal in Comparison to other technologies. In order to examine the behavior and to establish the trends in carbon dioxide sorption, NaX zeolite (Si/Al = 1.15) and it's the modified forms with identical degree (55.5 +/- 2.5) of exchange by K+, Rb+ and Cs+ cations have been selected., The samples were characterized by powder XRD, Low temperature nitrogen adsorption/desorption measurements, chemical analysis and also for the intermediate electronegativity and the partial charges on the atoms using Sanderson's electronegativity equalization principle. The isotherms of carbon dioxide using these NaX, NaKX, NaRbX and NaCsX samples were measured at an interval of 30 K in the temperature range of 273 to 363 K up to 600 Torr. The uptake of CO2 was found to depend on both, the size of the nonframework cation and the temperature at which the isotherms were measured. The cations with lower charge density will have lower extent of electrostatic interaction with the sorbate molecules. Since CO2 has more linear quadrupole moment, it interacts mainly with the extra-framework cations and framework oxygen. The carbon dioxide sorption data satisfactorily represented by Langmuir and also analyzed for the chemical affinity. The Isosteric heat (q(st)) of NaX for the coverage of 20 molecules per unit cell is nearly equal to 26 kJ, mol(-1). The NaX and NaKX comparatively show a flat heat profile with the increasing amount sorbed than those of NaRbX and NaCsX indicating a balance between the strength of energetic heterogeneity of sorbate-sorbent interactions and sorbate-sorbate interactions.
Keywords: CO2 sorption; Ionic exchange; Isosteric heat; NaX zeolite; Theoretical models

Effect of preparation parameters on characterization and activity of Co3O4 catalyst in liquid phase oxidation of lignin model substrates - Mate, Vivek R.; Jha, Ajay; Joshi, U. D.; Patil, K. R.; Shirai, M.; Rode, C. V. (Applied Catalysis A-General, 2014)
The nano structured spinel cobalt oxide (Co3O4) was prepared via simple co-precipitation method and its catalytic activity was evaluated for the liquid phase aerobic oxidation of lignin sub structure compounds such as veratryl alcohol. Catalyst preparation parameters influenced its morphology eventually affecting its oxidation activity. Thus, nano rod shaped CO3O4 catalyst showed 75% and 38% conversion of veratryl alcohol with complete selectivity to veratryl aldehyde in toluene and water, respectively, under base free condition. The influence of reaction conditions, such as temperature, oxygen pressure and catalyst loading was studied to obtain the optimum product yield and selectivity to the desired product. Furthermore, oxidation of various sub-structures of lignin model compounds was also studied over the same catalyst which was found to be in the following order: secondary alcohol >di-substituted > tri-substituted > monosubstituted > non-substitution. The stability of the catalyst was confirmed by its successful recycle for three times. (c) 2014 Elsevier B.V. All rights reserved.
Keywords: Coniferyl alcohol; Nano Co3O4; Sinapyl alcohol; TPR; Veratryl alcohol